2020
DOI: 10.21203/rs.3.rs-128597/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimality in COVID-19 vaccination strategies determined by heterogeneity in human-human interaction networks

Abstract: Interactions between humans cause transmission of SARS-CoV-2. We demonstrate that heterogeneity in human-human interactions give rise to non-linear infection networks that gain complexity with time. Consequently, targeted vaccination strategies are challenged as such effects are not accurately captured by epidemiological models assuming homogeneous mixing. With vaccines being prepared for global deployment determining optimality for swiftly reaching population level immunity in heterogeneous local communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Six studies reported that the trade-off between direct and indirect protection is sensitive to the proportion of people vaccinated. [12] [9] [21] [22] [15] [32] These papers stated that when vaccine supply is very low vaccination has a minimal impact on interrupting transmission, so more deaths can be prevented to vaccinate groups at risk of severe disease (e.g., key workers, seniors and clinical risk groups). However, as supply increases, this opens up the possibility of interrupting transmission, which can change prioritisation to the young or those with many contacts.…”
Section: Factors That Influence Prioritisation Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies reported that the trade-off between direct and indirect protection is sensitive to the proportion of people vaccinated. [12] [9] [21] [22] [15] [32] These papers stated that when vaccine supply is very low vaccination has a minimal impact on interrupting transmission, so more deaths can be prevented to vaccinate groups at risk of severe disease (e.g., key workers, seniors and clinical risk groups). However, as supply increases, this opens up the possibility of interrupting transmission, which can change prioritisation to the young or those with many contacts.…”
Section: Factors That Influence Prioritisation Strategymentioning
confidence: 99%
“…Seven studies recommended vaccination prioritisation based on social or occupational interactions compared to age group prioritisation. [28] [27] [31][32] [36][14] [37] Of these, three studies recommended prioritising essential workers to minimise cases[28] [27][14] and four studies recommended prioritising high social contact adults compared to other age groups. [31] [32] [37] [36]…”
mentioning
confidence: 99%
“…administer the vaccinations, and whether there is a strong healthcare infrastructure, sufficient funding and a system for vaccination monitoring [8]. The common strategies are aimed to reduce the mortality, decrease the pressure on the healthcare, and minimize the infection spread over a specific period of time [5].…”
Section: Discussionmentioning
confidence: 99%
“…Various levels of pre-existing immunity were also assumed, ranging from 5% to 20%, depending on the region. In [ 75 ], the authors studied the optimal choice of vaccination strategy under a partial or complete lockdown. Each of the individuals appearing in their model had a pre-assigned daily routine, specified on the resolution of 1 hour, with the routine determining the order in which the individuals move between different locations, such as workplaces, schools, public places, hospitals and homes.…”
Section: State Of the Artmentioning
confidence: 99%